GREEN MARKETING AND SUSTAINABILITY OF SMES BUSINESS: THE ROLE OF ENVIROPRENEURIAL ORIENTATION AS MEDIATING VARIABLE - Dahlia Amelia (RADJA PUBLIKA, 2026)
Purpose: This study aims to test and analyze the influence of green marketing on the sustainability of MSME businesses through environmental orientation. Design/methodology/approach: The sample for this study was SMEs registered with the Tangerang City Department of Industry, Trade, Cooperatives, and Small and Medium Enterprises (Disperindagkop UKM) using a combination of the Slovin and purposive sampling methods. Based on Tangerang City Government data as of March 2024, 58,692 MSMEs had obtained business identification numbers. Using this data collection technique, 100 final respondents were selected for further analysis to test the hypotheses. The data analysis technique used structural equation modeling-partial least squares (SEM-PLS). Findings: The results of this study found that green marketing has a positive and significant effect on environmental orientation, environmental orientation has a positive and significant effect on the sustainability of SMEs businesses, green marketing has a positive and significant effect on the sustainability of SMEs businesses, and environmental orientation can mediate the effect of green marketing on the sustainability of SMEs businesses. Originality/value: This study offers an original contribution by examining the role of environmental orientation as a mediating variable in the relationship between green marketing and the limited business sustainability of SMEs. This contrasts with previous research, which generally emphasizes the direct influence of green marketing on SMEs business sustainability. This study demonstrates that SMEs business sustainability is more effectively achieved when green marketing is able to shape an environmentally-based entrepreneurial orientation. This research also enriches the literature on the context of MSMEs in developing countries, particularly at the urban level, and expands the application of the Resource-Based View (RBV) by positioning green marketing as a strategic resource that drives SMEs internal capabilities to achieve business sustainability.